Antropología - Ember, Carol R.; Ember, Malvin; Peregrine, Peter (Madrid : Prentice Hall, 2004)
El CD-Rom muestra videos y texto sobre la evolución humana
incluye mapas
Keywords: ANTROPOLOGÍA CULTURAL -- AUDIOVISUAL; EVOLUCIÓN -- AUDIOVISUAL; ETNOLOGÍA -- AUDIOVISUAL